2013
DOI: 10.1111/maps.12111
|View full text |Cite
|
Sign up to set email alerts
|

Space weathered rims found on the surfaces of the Itokawa dust particles

Abstract: Abstract-On the basis of observations using Cs-corrected STEM, we identified three types of surface modification probably formed by space weathering on the surfaces of Itokawa particles. They are (1) redeposition rims (2-3 nm), (2) composite rims (30-60 nm), and (3) composite vesicular rims (60-80 nm). These rims are characterized by a combination of three zones. Zone I occupies the outermost part of the surface modification, which contains elements that are not included in the unchanged substrate minerals, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
158
4
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(188 citation statements)
references
References 64 publications
25
158
4
1
Order By: Relevance
“…Surfaces of extraterrestrial natural samples directly irradiated by solar wind are covered by a deposition layer tens of nanometers in thickness (Keller and McKay, 1993;Noguchi et al, 2014). On the other hand, deposition layers have not been observed in Genesis samples (Calaway et al, 2009), although an organic film contamination layer ("brown stain") has been observed on some Genesis samples.…”
Section: Resultsmentioning
confidence: 97%
“…Surfaces of extraterrestrial natural samples directly irradiated by solar wind are covered by a deposition layer tens of nanometers in thickness (Keller and McKay, 1993;Noguchi et al, 2014). On the other hand, deposition layers have not been observed in Genesis samples (Calaway et al, 2009), although an organic film contamination layer ("brown stain") has been observed on some Genesis samples.…”
Section: Resultsmentioning
confidence: 97%
“…1 and 2 ) indicates that cratered surfaces exposed to the Sun are subject to solarwind accumulation. Previous investigations of the solar-flare track density showed that regolith particles spend up to of order 10 3 to 10 4 yr in the top few centimeters of Itokawa's surface ( Keller and Berger, 2014;Noguchi et al, 2014 ), which yields an upper limit to T . Measurements of solar-wind noble gases indicate that Itokawa particles were directly exposed to the space environment for 150-550 yr ( Nagao et al, 2011 ).…”
Section: Origin Of Submicrometer Cratersmentioning
confidence: 99%
“…1 B and 2 B-F). The spotted structures are probably blisters, which are thought to have formed through accumulation of solar-wind-entrained hydrogen and helium implanted within 60-80 nm ( Noguchi et al, 2014;Matsumoto et al, 2015 ). The blisters might have developed through solar wind irradiation within the order of 10 3 years ( Noguchi et al, 2014 ).…”
Section: Crater Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Itokawa particles well preserve space-weathering and surface irradiation processes on their surfaces (e.g., Noguchi et al, 2011Noguchi et al, , 2014Busemann et al, 2014), and thus the surface structures and chemical and isotopic compositions of the returned particles from 1999 JU 3 will be carefully investigated to understand space-weathering and surface irradiation on the surface of C-type asteroids for the first time. Thermal metamorphism at the surface of this near-Earth asteroid will also be studied because it may have once had a perihelion smaller than 1 AU (Michel and Delbo, 2010), combined with temperature data obtained by TIR and MAS-COT, which could provide a constraint on the orbital evolution of 1999 JU 3 in the inner solar system (e.g., the maximum temperature and duration).…”
Section: Orbital Evolution and Surface Geological Processes Of A Nearmentioning
confidence: 99%